Body, Memory and Systemic Violence: Perspectives on Annie Ernaux’s L’Événement - Pena López, Claudia (Thélème. Revista Complutense de Estudios Franceses, 2026)
Annie Ernaux’s writing has introduced the voice and reality of women into a literary universe long dominated by a male perspective. In L’Événement, Ernaux paints a portrait of a French medical system that reveals a society profoundly violent towards women. It was through the determination of Ernaux and many anonymous women that abortion was finally legalized. This article analyzes the multiple forms of violence suffered by the protagonist, highlighting the inseparable links between social class and gender, illustrating an intersectional approach and an intellectual activism that unites her female readers within a feminist sisterhood supported by her literary work.